1992
DOI: 10.1148/radiology.185.2.1410362
|View full text |Cite
|
Sign up to set email alerts
|

Inverted papilloma: evaluation with MR imaging.

Abstract: The authors examined the magnetic resonance (MR) appearance of inverted papillomas to determine if this histologically benign lesion could be distinguished from malignancies of the sinonasal cavity. MR images in 10 patients with histologically proved inverted papilloma were retrospectively reviewed. The signal intensity of inverted papillomas on short repetition time (TR) images was iso- to slightly hypertintense to muscle in all 10 patients. Inverted papillomas had intermediate signal intensity on the long TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 0 publications
2
38
0
3
Order By: Relevance
“…It would be useful for planning therapeutic strategies if the CCP on MR imaging can suggest the preoperative diagnosis of IP, because more aggressive surgical approaches would be needed for IPs concomitant with SCC and other malignant sinonasal tumors. However, one previous study reported by Yousem et al 13 failed to find this sign as a specific MR imaging finding to diagnose IP. The purpose of this study was to evaluate the diagnostic accuracy of a CCP depicted on MR imaging for distinguishing IP from other malignant sinonasal tumors in a relatively large number of patients.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…It would be useful for planning therapeutic strategies if the CCP on MR imaging can suggest the preoperative diagnosis of IP, because more aggressive surgical approaches would be needed for IPs concomitant with SCC and other malignant sinonasal tumors. However, one previous study reported by Yousem et al 13 failed to find this sign as a specific MR imaging finding to diagnose IP. The purpose of this study was to evaluate the diagnostic accuracy of a CCP depicted on MR imaging for distinguishing IP from other malignant sinonasal tumors in a relatively large number of patients.…”
mentioning
confidence: 81%
“…[3][4][5][6][7][8][9][10][11][12] Although CT and MR imaging are useful for preoperative assessment of sinonasal IP, differentiation of IP from other malignant sinonasal tumors is often difficult because of a significant overlap of the imaging features. [13][14][15][16][17][18][19] Barnes et al 20 described a distinctive gross mucosal morphology of IP, a so-called convoluted cerebriform pattern (CCP), which can be reflected on MR imaging by the characteristic alternating hypointense and hyperintense bands on T2-weighted and contrast-enhanced T1-weighted images, as reported by Ojiri et al 17 and supported by Maroldi et al 19 years later. It would be useful for planning therapeutic strategies if the CCP on MR imaging can suggest the preoperative diagnosis of IP, because more aggressive surgical approaches would be needed for IPs concomitant with SCC and other malignant sinonasal tumors.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…The main utility of MRI is in defining the extent of the lesion and differentiating inverted papilloma from inspissated mucus. 2,38 Magnetic resonance imaging is ideal for assessment of intra-cranial and intra-orbital tumour extension. 6 Early osteitic changes appear hypointense on T1-weighted images and hyperintense on T2-weighted images.…”
Section: Computed Tomographymentioning
confidence: 99%